New plant records for the Marathwada region of Maharashtra, India - S.P. Gaikwad; R.D. Gore; K.U. Garad; S.D. Randive (Journal of Threatened Taxa, 2014)
Floristic investigation of Balaghat ranges, resulted in an addition of ten flowering plants not previously recorded from Marathwada region. A brief taxonomic description along with distribution, phenology and GPS data is provided for each taxon.